A Brief Review of Infrequent Spontaneous Findings, Peculiar Anatomical Microscopic Features, and Potential Artifacts in Göttingen Minipigs. (April 2016) - McInnes, E. F.; McKeag, S.
Minipigs are now used in greater numbers in contract research organizations (CROs) as well as in the pharmaceutical industry. Most CROs or pharmaceutical companies use the Göttingen minipig, which displays a number of important background lesions. This review will discuss some of the more infrequent minipig background changes. Porcine stress syndrome is an autosomal recessive pharmacogenetic disorder in minipigs causing malignant hyperthermia and muscle necrosis. Possible triggers, clinical pathology as well as heart, muscle, liver, lung, and kidney histopathology are discussed. Additional spontaneous changes, background findings, and peculiar anatomical and histological features include thrombocytopenic purpura syndrome, spontaneous glomerulonephritis, osteochondritis, ellipsoids, or Schweigger–Seidel sheaths in the spleen, as well as the presence of a perimesenteric plexus adjacent to mesenteric lymph nodes, squamous epithelial metaplasia of the salivary gland, and cupping of the optic disk in the minipig eye. In order to maximize the data gained from minipig studies, the interpretation of pathology findings requires the input of experienced pathologists who understand the significance of artifacts and spontaneous, background lesions in minipigs and can distinguish these from induced lesions.